2021
DOI: 10.1159/000518395
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Development of the Fecal Microflora of South China Tiger Cubs (<b><i>Panthera tigris amoyensis</i></b>) by Sequencing of the 16S rRNA Gene

Abstract: Postnatal colonization and development of the gut microbiota is linked to health and growth. A comprehensive understanding of the postnatal compositional changes and development of the microbial community is helpful to understand the gut health and improve the survival rate of South China tiger cubs (<i>Panthera tigris amoyensis</i>). Fecal samples from three tiger cubs were collected on the day of birth in 2018 (June 17–21 [G0], July 18 [G1], July 31 [G2], and August 7 [G3]). The 16S rRNA genes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
3
2
0
Order By: Relevance
“…Previous studies have reported similar bacterial genera associated with the gut microbiota of the genus Panthera , although some previously-reported genera were not isolated in the present study ( Hua et al 2020 , Mittal et al 2020 , Chen et al 2022 ). The findings of this study are consistent with earlier research on carnivores, particularly the genus Panthera ( Ning et al 2020 , Jiang et al 2020 , Sun et al 2021 ). From the 201 genera isolated from the faecal matter of the genus Panthera in Zoo Melaka, some contained non-pathogenic species.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported similar bacterial genera associated with the gut microbiota of the genus Panthera , although some previously-reported genera were not isolated in the present study ( Hua et al 2020 , Mittal et al 2020 , Chen et al 2022 ). The findings of this study are consistent with earlier research on carnivores, particularly the genus Panthera ( Ning et al 2020 , Jiang et al 2020 , Sun et al 2021 ). From the 201 genera isolated from the faecal matter of the genus Panthera in Zoo Melaka, some contained non-pathogenic species.…”
Section: Discussionsupporting
confidence: 92%
“…Actinobacteria also contributed to the gut microbiota of the tigers, which might play a role in maintaining host homeostasis, inhibition of Gram-negative pathogens, and lactic acid fermentation ( Colston and Jackson, 2016 ). The gut microbiome of SC within 2 months old ( Sun et al, 2022 ) was found to occupy the similar predominant phyla as we found in this study. However, the genus that was reported in the gut of those tigers was much different from what we found here, except for the genus of Collinsella and Campylobacter , which were found in both samples ( Supplementary Table 5 ; Sun et al, 2022 ).…”
Section: Discussionsupporting
confidence: 82%
“…The gut microbiome of SC within 2 months old (Sun et al, 2022) was found to occupy the similar predominant phyla as we found in this study. However, the genus that was reported in the gut of those tigers was much different from what we found here, except for the genus of Collinsella and Campylobacter, which were found in both samples (Supplementary Table 5; Sun et al, 2022). This might indicate that the structure of the gut microbiome of SC changed more dramatically in the early period after birth, and after 1 year old, it became more stable.…”
Section: Southern China Tiger Gut Microbiome Is Dominated By Bacteria...supporting
confidence: 84%
See 2 more Smart Citations